Factors influencing the incidence and prognosis of canine rnarnmary tumours - Pérez Alenza, M. D.; Peña, L.; del Castillo, Noemí; Nieto, A. I. (Wiley, 2025)
Factors relating to the incidence of canine mammary tumours are reviewed. Increased age, intact status or ovariectomy after 2.5 years of age, as well as progestagen treatment, can all lead to an increased risk of mammary neoplasia in the bitch. In addition, obesity early in life, and a habitual diet based on home-made food (rich in beef and pork, and poor in chicken) as opposed to commercial food, are also associated with the occurrence of mammary tumours. Other aspects related to incidence are also discussed. Increased age at diagnosis, invasive growth (fixed to adjacent tissues), large tumour size, ulceration of skin, and axillary or inguinal node involvement are clinical parameters associated with a low chance of survival after surgical excision of mammary tumours. Histological typing and grading of the tumour allows the establishment of a prognosis, which is poor where there is tumour proliferation as measured by S-phase fraction determination and Hi-67 immunostaining.